Les IUT : de l'autonomie à la subordination ? - Catherine Agulhon
IUT's have developped alongside universities on more or less specific lines. Their ties with the universities were distant while those with their tutelage, the minister of further education, were much closer. Less secondary than the STS, they have diplomas and subject matter defined on a national level, half the teaching staff recruted as PRAG come from secondary schooling, a visible demand for their students and an autonomous financial organisation, being able to count on apprenticeship taxes and comfortable ressources from adult training. The Bologne process, then the LRU bring them back to the influence of the universities provoking worry and tension. Can the IUT's keep their independance when their finances and choice of positions pass by the redistribution handed out by the university councils? Will they lose their reputation and specificity?